DETERMINANTS OF PUBLIC COMPLIANCE IN FACE MASK WEARING TO PREVENT COVID-19 TRANSMISSION IN INDONESIA - Sri Handayani; Syarifah Nuraini; Indah Pawitaningtyas; Aan Kurniawan (International Journal of Public Health Science (IJPHS), 2022)
To tackle the COVID-19 case, the COVID-19 task force in Indonesia urges the public to carry out COVID-19 prevention behaviours including wearing masks. To find the determinants factors that affect public compliance with using masks, an online survey was conducted in Indonesia from 27 June to 7 July 2020. The analytical technique used in this study consisted of descriptive and inferential analysis. Of the 8,425 respondents, the majority (67.1%) had moderate mask compliance. Age, gender, education, income and risk of infection have a significant relationship with mask compliance. Female respondents have higher compliance of wearing masks than men. Most respondents with high compliance in wearing masks are highly educated and have high incomes. The Boomer (elderly) group has the highest percentage who has low adherence to wearing masks. Respondents who stated they might be at risk of contracting COVID-19 had a high compliance score for wearing masks compared to respondents who stated they were unlikely to be infected. Socio-demographic factors significantly influence compliance with the use of masks during the COVID-19 pandemic in Indonesia. To improve compliance with the implementation of health protocols, the government needs to provide socialization, supervision, and evaluation to implement health protocols in the community.